El motivo del tiempo en Stichus de Plauto - Moro, Stella Maris; Martí, María Eugenia (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2020)
Duckworth recognizes three constitutive fabulae in Stichus. This paper analyzes the role that time plays in each one of them: first, the conflict provoked by a different perspective assumed regarding the mutability or immutability of social relations, institutions such as marriage and values such as pietas; second, the parasitus’ complaints around the current times of hunger and shortage, opposed to a "generous" past of banquets; finally, a day of freedom granted to slaves, a space for ephemeral celebration, which transience implies the imminence of the return to the established social order.